2013
DOI: 10.1136/bcr-2013-008581
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis-related cholecystitis

Abstract: Acute cholecystitis is a common inflammatory condition of the gallbladder caused most commonly byEscherichia coli,Enterococcus, andKlebsiellaorganisms. Streptococcus bovisis a Gram-positive, catalase-negative, anaerobic coccus found as a commensal inhabitant of the digestive system in 16% of healthy people. We report a rare case of acute cholecystitis caused byS bovisand discuss its implications with regard to the two knownS bovisbiotypes (I & II) both of which are associated with a number of other gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There are few reported cases of biliary tract infection caused by SBG [13][14][15][16]. A possible explanation is that in previous publications about a-haemolytic streptococci, the bacteria were rarely identified to the species level in intrabdominal samples and, in studies about group D streptococci, both enterococci and SBG were often grouped together [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few reported cases of biliary tract infection caused by SBG [13][14][15][16]. A possible explanation is that in previous publications about a-haemolytic streptococci, the bacteria were rarely identified to the species level in intrabdominal samples and, in studies about group D streptococci, both enterococci and SBG were often grouped together [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Over 20 years ago, Ruoff et al [12] reported the association between S. bovis biotype II and biliary tract infections. Since then, this association has received little attention [13][14][15][16]; the percentage of SBG bacteraemia with biliary origin has been estimated in several reports at between 0 and 38% [17][18][19][20][21][22][23][24][25][26][27]. However, the features associated with this infection, risk factors, underlying diseases, and the relationship with the new taxonomic species of SBG has not been well determined.…”
Section: Introductionmentioning
confidence: 99%